1995
DOI: 10.1080/01904169509365025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of VAM on phosphorus nutrition of maize with low soluble phosphate fertilization

Abstract: In a greenhouse pot experiment, maize was grown inoculated with the spores of the VAM fungi Glomus mosseae and Glomas multicaulis or non-inoculated. Low soluble ferrous phosphate (FePO 4 . 4 H 2 O) was added to the mycorrhized and non-mycorrhized maize. The fresh and dry weights of mycorrhized plants with added phosphate (P) were higher than in mycorrhized plants without added P or non-mycorrhized plants with added P. The amount of P in the soil samples from pots with mycorrhizal plants fertilized with P was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Phosphorus mobilization by AMF may involve both Pi (Smith and Read, 2008) and Po forms (Andrino et al, 2020). There is also evidence that AMF can desorb OP from ferrihydrite (Gogala et al, 1995;Rakshit and Bhadoria, 2010), and recently, we confirmed the ability of R. irregularis to mobilize Po and Pi bound to goethite (GOE), one of the most abundant Fe (oxy)hydroxides in tropical soils, at differing host plant C cost (Andrino et al, 2019).…”
Section: Introductionsupporting
confidence: 67%
“…Phosphorus mobilization by AMF may involve both Pi (Smith and Read, 2008) and Po forms (Andrino et al, 2020). There is also evidence that AMF can desorb OP from ferrihydrite (Gogala et al, 1995;Rakshit and Bhadoria, 2010), and recently, we confirmed the ability of R. irregularis to mobilize Po and Pi bound to goethite (GOE), one of the most abundant Fe (oxy)hydroxides in tropical soils, at differing host plant C cost (Andrino et al, 2019).…”
Section: Introductionsupporting
confidence: 67%
“…In this study, mycorrhizal and non-mycorrhizal plants were grown under prolonged sulfur deficiency in the presence of insoluble iron, as FePO 4 salt. This salt has been used in previous studies, as practically insoluble form of phosphate, for the investigation of the impact of AM fungi on plant growth or P nutrition (Bolan et al, 1987 ; Virant-Klun and Gogala, 1995 ). In our study FePO 4 had a dual role: it was the only source for Fe and the main source for P as the nutrient solution provided was P insufficient in order to promote the establishment of mycorrhizal symbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…As stated by Coffman and Bates (1993), "Breeding for sustainability is a process of fitting appropriate crops and cultivars to an appropriate environment instead of altering the environment through inputs such as fertilizer, water, and pesticides." Since crops in sustainable agricultural systems need to be resource efficient, crop improvement should consider mycorrhizal symbiosis potential (Johnson and Pfleger, 1992;Callaway and Francis, 1993) in implementation strategies, as phosphorus (P) nutrition is the most pronounced and well-documented benefit of mycorrhiza (Virant-Klun and Gogala, 1995;Lu and Miller, 1989;Khan, 1972;Khalil et al, 1994Khalil et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%